(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study attempts to explore the Role of Knowledge Management (KM) in Indian IT sector by identifying a definition, components and exemplar of knowledge management adopter in IT sector. The paper undertakes critical literature review to analyse different academic research paper on KM and KM in IT sector. The result demonstrates that organization culture and suitable strategy for KM largely influence the implementation and practice of KM in IT firms of India. The findings also contribute to existing knowledge in KM and guide scholars for further research on KM in Information technology domain.